Caracterização morfológica dos estádios de desenvolvimento do aparelho reprodutor feminino da rã-touro, Rana catesbeiana, no sistema anfigranja de criação intensiva - Costa, Ciniro [UNESP]; Lima, S. L.; Andrade, D. R.; Agostinho, Claudio Angelo [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1998)
The objective of this work was to caracterize the morphological characterization of the development stages of female reproduction apparel of bullfrog Rana catesbeiana from intensive Anfigranja system. During the period of one year, 836 bullfrog females were removed from regrowing and reproduction sections of the Anfigranja system to study the basic aspects of the reproduction of this specie. The collections were realized monthly and, in that occasion, the body and ovary weights for each animal were recorded and their macroscopic gonadal characteristics, registred. The ovaries from 303 females were removed and histologically examined. From the macro and microscopic characteristics analysis set of the ovary, five stages of gonadal maturation for the female of Rana catesbeiana were determined: juvenile, beginning of maturation, intermediate maturation, advance maturation and spent.
Morphological characterization of the development stages of female reproduction apparel of bullfrog, Rana catesbeiana, in the intensive Anfigranja systems
Keywords: captivity; stages; females gonads bullfrog; reproduction